2012
DOI: 10.2151/jmsj.2012-604
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Energy Budget Analysis on the Development of a Meso-β-Scale Vortex Causing Heavy Rainfall, Observed over Aomori Prefecture in Northern Japan on 11 November 2007

Abstract: On 11 November 2007, record heavy rainfall was observed over Aomori Prefecture in northern Japan. Numerical simulations were performed using a non-hydrostatic model with a horizontal resolution of 5 km (5km-NHM) to clarify the formation mechanisms of this heavy rainfall. The results revealed that a meso-β scale vortical disturbance (MβV) originated over the offshore area with strong horizontal wind shear southeast of Aomori Prefecture at 0600 UTC 11 November. The MβV traveled north-northwestward over the sea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The environmental conditions necessary to develop QSCSs, particularly during the Baiu season, are characterized by a larger moisture content (Kato, ; Hirockawa and Kato, ). Higher environmental moisture may be a common feature for MCS events over East Asia; for example, Meng et al () showed that precipitable water is higher for the MCSs in east China than for those in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental conditions necessary to develop QSCSs, particularly during the Baiu season, are characterized by a larger moisture content (Kato, ; Hirockawa and Kato, ). Higher environmental moisture may be a common feature for MCS events over East Asia; for example, Meng et al () showed that precipitable water is higher for the MCSs in east China than for those in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of these events (e.g., Syono et al 1959;Ogura et al 1985;Watanabe and Ogura 1987;Nagata and Ogura 1991;Ishihara et al 1995;Kato 1998; Kato and Goda 2001;Kato 2006) have clarified the formation and maintenance mechanisms of heavy rainfall events during the Baiu season. However, heavy rainfall events occurring outside the Baiu season have been little studied (e.g., Seko et al 1999;Tsuguchi and Sakakibara 2005;Hirockawa and Kato 2012), and their formation and maintenance mechanisms are less well understood.…”
Section: Introductionmentioning
confidence: 99%